Acerca da família nuclear - Ribeiro, Paulo Marcio de Castro (1985)
This work is motivated by a basic, present and actual question: The nuclear family would be undergoing a transformation in its organization. Specifically, the dissoloubility of the marriage knots would be contributing to a different arrangement of the terms of relation ship. As we tried to demonstrate in this work, the brazilian family model as defined by the church and the 'hygien model' is de characterized by a kind of affective relationship which is different than the one found in traditional marriages - 'until death us appart'. This issue extends itself into the following question: 1s the family organization changing with history, i.e., through the different social formations, or the nuclear family, object of our research, has been an ever-existing since man became civilized. With its restricted family ties and variations which would be only mere exceptions and deviations of the standard restricted family model, as some authors want to? Our answer to this question is clearly favourable to the point of view wich affirms the transformation of the familiar organization, through the time, therefore through the history, and what is more important, through different social formations. Thus we were compelled, not only because our practice, but chiefily by the in time connection that historical research reveals between the spring of psychoanalisis and the sedimentattion of the model of the nuclear family by the new power of 'handling life', that is, a power that is interested in taking off the life all of the best it can give, a power to whom interesses an evermore greater quality of bodies, in order to explore the greater possible quantity of production. Family by itself is a problem, it is an instituition that constrains all the human sciences, even medicine, are obliged to face it in their practice, either being empirical or theorical. So as this it a theorical work it was necessary to go through several knowledges, the most remarkable ones in our point of view, to be able to achieve our objectives.